Hedging performance and multiscale relationships in the German electricity spot and futures markets - Mara Madaleno; Carlos Pinho (Journal of Risk and Financial Management, 2010)
We explore optimal hedge ratios and hedging effectiveness for the German electricity market. Given the increasing attention that wavelets received in the financial market, we concentrate on the investigation of the relationship, covariance/coherence evolution and hedge ratio analysis, on a time-frequency-scale approach (discrete and continuous), between electricity spot and futures. Simpler approaches are also used for comparison purposes like the näive, OLS and the dynamic multivariate GARCH model in order to account for risk reduction through hedging. Results allow us to conclude that: dynamic hedging strategies provide higher variance reductions in terms of hedging effectiveness; there is poor correlation among spot and futures, not being homogeneous across scales, which condition the effectiveness of the hedging strategy; the long-horizon hedge ratio does not converge to its long run equilibrium of one. Wavelets poor fit in variance reduction is attributed to low coherence and to statistical relationships between spot and futures electricity series. The instability found in various aspects of market comovements may imply serious limitations to the investor's ability to exploit potential benefits from hedging with futures contracts in electricity markets. Moreover, much variation in the contemporaneous relationship among spot and futures may highlight inadequacy in assuming (short-term) relationships in both markets, which might account for the difficulty in achieving profitable active trading.
Keywords: C32; G10; 330; Dynamic and Static Hedging; Electricity Futures and Spot Prices; Discrete and Continuous Wavelets Coherence and Phase; Optimal Hedge Ratio; Multivariate GARCH